2020
DOI: 10.3389/fonc.2020.01142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 9-Core Immune-Related Genes in Bladder Urothelial Carcinoma Prognosis

Abstract: Background: Immune microenvironment within tumors affects initiation, progression and clinical outcome of human cancers. Here we explored an immune-related gene signature associated with prognosis of patients with bladder urothelial carcinoma. Method: The Cancer Genome Atlas (TCGA) database was interrogated for expressions of immune-related genes in bladder urothelial carcinomas. Integrated bioinformatics analyses were performed to identify prognostic factors. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…but its expression and function in BC are still unclear. Recently, some studies have used databases to analyze the prognostic relevance of Rac3 in BC [23][24][25][26][27], but strict inclusion criteria were in place for the patients with BC in this study, and the number of patients we analyzed was different. We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…but its expression and function in BC are still unclear. Recently, some studies have used databases to analyze the prognostic relevance of Rac3 in BC [23][24][25][26][27], but strict inclusion criteria were in place for the patients with BC in this study, and the number of patients we analyzed was different. We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis. Qiu et al [23] and Liu et al [24] screened only prognostic immune-related genes with univariate Cox analysis, while Na et al [25] and Tang et al…”
Section: Discussionmentioning
confidence: 99%
“…SH3 domain-binding protein 2 (SH3BP2) is a pathogenic gene of Cherubism and some studies have suggested that its protein was helpful to regulate the signaling pathway of B cells and macrophages in the immune system. However, its role in cancer is still unclear, several studies have found that SH3BP2 was a protective factor ( 57 59 ) and may be a tumor suppressor gene in bladder cancer ( 60 ). In our study, these two genes were also found to be protective factors, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 mRNA expression was higher in invasive UC than that in super cial UC [46]. Besides, Lei et al [8] revealed MMP9 could promote cancer invasion, metastasis and angiogenesis, while its expression was correlated with UC grade, invasiveness and poor prognosis. Wu et al [47] found that the Wnt signaling pathway would regulate UC metastasis through activating MMP9, and showed that MMP9 may be regulated by miR-3713 in UC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more studies focus on the roles of immune checkpoint inhibitors (ICIs) and immunocytes in pathogenesis, immunotherapy of cancer, as well as disease progression [7]. Interaction between tumor cells and immunocytes suppressed immune response and promoted tumor progression [8][9][10]. In 1976, Bacillus Calmette-Guerin was rst used as an immune agent for treating UC [11] as it showed anti-tumor effects by activating the immune system and inducing in ammatory reaction [12].…”
mentioning
confidence: 99%